Suplementasi Air Cucian Beras dan Belerang Sebagai Sumber Mineral Esensial Alami Untuk Meningkatkan Kecernaan Pakan Jerami Padi Amoniasi Secara In Vitro - Firgian Ardigurnita; Putri Dian Wulansari; Nurul Frasiska (Bulletin of Applied Animal Research, 2023)
The aim of this study was to obtain the best combination of levels of rice washing water and sulfur supplementation to increase the digestibility of ammoniated rice straw feed. The material for this research was ammoniated rice straw, sulfur as a source of mineral S and rice washing water as a source of mineral P. The study used a completely randomized design with 3 treatments and 6 replications. As a treatment: P0 = 1 kg rice straw + 6% urea; P1 = 1 kg rice straw + 6% urea + 50% rice washing water + 0.2% sulfur; P2 = 1 kg rice straw + 6% urea + 50% rice washing water + 0.4% sulfur. Then the feed samples were analyzed for their characteristics and digestibility which included: dry matter digestibility (KcBK), organic matter digestibility (KcBO), and N-NH3 in vitro. The results showed that the average KcBK value from P0, P1 and P2 was 39.44 ± 0.86; 47.23 ± 3.26 and 57.26 ± 0.85. The mean value of organic matter digestibility from P0, P1 and P2 was 44.74 ± 0.58; 55.63 ± 2.96 and 67.72 ± 0.38. The mean value of N-NH3 respectively from P0, P1 and P2 is 1.76 ± 0.10; 2.63 ± 0.79 and 4.11 ± 0.26. The results of the analysis showed that the addition of rice washing water and sulfur to each treatment had a significant effect (P<0.05) on KcBK, KcBO and N-NH3. Keywords : Dry Matter, Organic Matter, Rice Straw, Amoniation.